2020
DOI: 10.1159/000509100
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Infarction with Nonobstructive Coronary Arteries (MINOCA): A Review of the Current Position

Abstract: Myocardial infarction with nonobstructive coronary arteries (MINOCA) remains a puzzling clinical entity that is characterized by clinical evidence of myocardial infarction (MI) with normal or near-normal coronary arteries on angiography (stenosis < 50%). Major advances in understanding this condition have been made in recent years. The precise pathogenesis is poorly understood and is being studied and examined further. Guidelines indicate that MINOCA is a group of heterogeneous diseases with different mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 62 publications
1
44
0
14
Order By: Relevance
“…Enormous studies are dedicated to the issue of MI occurrence in IHD patients, particularly early MI diagnostic [15][16][17][18][19]. However, there is limited data regarding risk factors for UA transformation toward MI [20].…”
Section: Discussionmentioning
confidence: 99%
“…Enormous studies are dedicated to the issue of MI occurrence in IHD patients, particularly early MI diagnostic [15][16][17][18][19]. However, there is limited data regarding risk factors for UA transformation toward MI [20].…”
Section: Discussionmentioning
confidence: 99%
“…Atrial fibrillation is the commonest embolic cause of MINOCA 7 (accounting for up to 3% of cases 2 ) and an independent risk factor. 6 10 Patients with metallic mitral valves and atrial fibrillation are regarded high risk for cardioembolism, warranting a target INR of at least 3, whereas those with no risk factors have a target of 2.5. 11 Her INR at presentation was therefore subtherapeutic ( Table 1 ) and could have been responsible for the event.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Among patients with MI, it has been found that up to 10 to 15% have normal coronary arteries on angiography. 1 3 4 5 6 This results in a diagnosis of MI with nonobstructive coronary arteries (MINOCA). MINOCA is a working diagnosis 3 4 5 6 7 8 with a predilection for younger non-white women (younger than 55 years) without traditional cardiovascular risk factors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations